ANALISIS BIMBINGAN KLASIKAL ONLINE DI KELAS VIII A SMP NEGERI 18 PONTIANAK TAHUN 2021 - Lisa Safitri; M Asrori; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the results of the analysis of online classical guidance in class VIII A SMP Negeri 18 Pontianak in 2021. The population in this study was class VIII students totaling 35 students, because the number of students was only 35 people, the entire population was used as research subjects. so that this research is a population study, the research method used is descriptive with a quantitative approach, while the data collection technique uses indirect communication techniques, namely using questionnaires that are distributed directly to class VIII A students at SMP Negeri 18 Pontianak. The results showed: 1) the form or stage of online classical guidance got an actual score of 210 and an ideal score of 252 with a percentage of 83% in the high category. 2) the online classical guidance material got an actual score of 308 and an ideal score of 420 with a percentage of 73% in the high category. 3) the online classical guidance method got an actual score of 143 and an ideal score of 258 with a percentage of 55% in the medium category. 4) online classical guidance media got an actual score of 219 and an ideal score of 378 with a percentage of 57% in the medium category. 5) the supporting and inhibiting factors of online classical guidance got an actual score of 208 and an ideal score of 420 with a percentage of 49% in the medium category.